Consumer protection in India : policies and case studies - National Seminar on "Consumer Protection in India: Lessons Learnt and Future Challenges" (2009 : New Delhi, India); Misra, Suresh; Chadah, Sapna; Pathania, Mamta, 1978- (New Delhi : Concept Pub. Co., 2012)
Papers presented at the National Seminar on "Consumer Protection in India : Lessons Learnt and Future Challenges", held at New Delhi in November 2009.
Includes bibliographical references and index.
Keywords: Consumer protection -- Law and legislation -- India -- Congresses; Consumer protection -- India -- Case studies -- Congresses